A study on factors that affect motivation among teachers in Sungai Petani, Kedah / Norsyazwani Ab Halim and Nurul Husnina Mokhtar - Ab Halim, Norsyazwani; Mokhtar, Nurul Husnina (2019)
Nowadays, the level of motivation among teachers is important in order to ensure the objective of the institutional can be achieved successfully. Therefore, this study was conducted to examine the factors that affect the motivation among teachers in Sungai Petani. This study focused on the discussion of the findings based on quantitative study. Data of this study were collected by a set of questionnaire containing six section, demographic data of respondents, motivation, workplace environment, empowerment, superior support and colleagues support. The sampling technique that have been used is census sampling. Data were analyzed by using Statistical Packages for the Social Sciences (SPSS) version 24. The result shows that workplace environment is the main factor that contribute to the motivation among teachers in Sungai Petani. The significance of this study is to contribute to the body of knowledge in the area of teachers’ behavior, to assist understanding of teachers’ motivation and to assist awareness for the teachers. The recommendation has been provided in this study is to increase the encouragement of empowerment among teachers in Sungai Petani. The discussion and conclusion are elaborated in this study.